Akulturasi Komunikasi Antar Budaya pada Hari Raya Besar Umat Kristen Bali di Desa Blimbingsari, Jembrana - Turker, Natasya Patriasari; Gelgel, Ni Made Ras Amanda; Suryawati, I Gusti Agung Alit; Damasemil, Calvin (E-Jurnal Medium, 2023)
This is a qualitative research with constructivist methods which was carried out because of the author's interest in the uniqueness and phenomena that happened in the Balinese Christian Village Blimbingsari, Jembrana. This phenomenon and uniqueness are the acculturation of Balinese culture/Bebalian with Christianity due to intercultural communication between Tsang To Hang as a Christian evangelists and Balinese people. This intercultural communication leads some of these Balinese people converted their faith into Christianity and incorporated Christian values ??into Balinese culture/Bebalian in their social and spiritual life. Based on this uniqueness and phenomena, this study aims to answer the question about acculturation forms of intercultural communication on Balinese Christian Religious Holy Days in Blimbingsari, Jembrana, especially on Passover Holy Day by using intercultural communication theory and Roland Barthes semiotics theory. The results of this study reveal that there are several forms of acculturation of Balinese culture /Bebalian with Christianity on Passover Day in Blimbingsari, Jembrana. These forms are the architecture and ornaments of church buildings as well as ornaments on the church equipment for Good Friday dan Passover observance. These forms also memenjor and nampah traditions, pajeng processions and traditional Balinese gamelan instrument and the application of traditional Balinese clothes in the Good Friday and Passover Holy Day observance, balaganjur on a grave pilgrimage, and also tamiang and lamak as a decoration in several corners of the GKPB “Pniel” Blimbingsari church. The acculturation of communication between Balinese culture/Bebalian with Christianity makes Passover Holy Day in Blimbingsari, Jembrana more unique and special.